Promoting physical activity within breast cancer survivors using behavior change techniques: N-of-1 randomized controlled trials - Sequeira, Margarida (2023)
This work received national funding from Fundação para a Ciência e a Tecnologia (FCT), I.P—through the Research Center for Psychological Science of the Faculty of Psychology, University of Lisbon (UIDB/04527/2020; UIDP/04527/2020).